Ephrin or not? Six tough questions on Eph targeting. (3rd May 2020) - Giorgio, Carmine; Zanotti, Ilaria; Lodola, Alessio; Tognolini, Massimiliano
ABSTRACT: Introduction : The Eph-ephrin is a cell-cell communication system generating a forward signal in cell expressing Eph receptors and a reverse signal in ephrin-ligand expressing cells. While clearly involved in the insurgence and progression of cancer, the understanding of the molecular mechanisms regulated by this system needs development; this is a hurdle to the development of therapeutic strategies that can target the Eph receptors and/or their ephrin ligands. Areas covered : We have taken the opportunity to share some key questions on the most effective strategies to target the Eph-ephrin system. This article is based on our experience of the field and therefore is a Perspective and not comprehensive examination of the literature. Expert opinion : Targeting of the Eph-ephrin system has emerged as a potentially valuable approach for cancer therapy. Pharmacological tools have been reported in the last 15 years and these include forward signaling blockers such as kinases inhibitors and antagonists of forward and reverse signaling. Also, biologics including antibodies and recombinant proteins have been developed and some have reached early clinical stages. Data deem the Eph-ephrin system as a signaling axis that is an elusive target. A better understanding of the basic pharmacology behind the activity of available agents and a comprehensive knowledge of the ephrin biology are necessary. We are looking forward to knowing the opinion of the readers.